The Gods, the State, and the Individual : Reflections on Civic Religion in Rome - Scheid, John (Book collections on Project MUSE., 2016)
Roman religious practice has long presented a number of challenges to historians approaching the subject from a perspective framed by the three Abrahamic religions. The Romans had no sacred text that espoused its creed or offered a portrait of its foundational myth. They described relations with the divine using technical terms widely employed to describe relations with other humans. Indeed, there was not even a word in classical Latin that corresponds to the English word religion. In The Gods, the State, and the Individual, John Scheid confronts these and other challenges directly. If Roman religious practice has long been dismissed as a cynical or naïve system of borrowed structres unmarked by any true piety, Scheid contends that this is the result of a misplaced expectation that the basis of religion lies in an individual's personal and revelatory relationship with his or her god. He argues that when viewed in the light of secular history as opposed to Christian theology, Roman religion emerges as a legitimate phenomenon in which rituals, both public and private, enforced a sense of communal, civic, and state identity. Since the 1970s, Scheid has been one of the most influential figures reshaping scholarly understanding of ancient Roman religion. The Gods, the State, and the Individual presents a translation of Scheid's work that chronicles the development of his field-changing scholarship.